Impulse Responses Measured with MLS or Swept-Sine Signals Applied to Architectural Acoustics: An In-depth Analysis of the Two Methods and Some Case Studies of Measurements Inside Theaters. (November 2015) - Guidorzi, P.; Barbaresi, L.; D'Orazio, D.; Garai, M.
Abstract: The measurement of impulse responses inside of a room or a theatre is a critical task in architectural acoustics. The impulse responses are usually measured using either Exponential Sine Sweep (ESS) or Maximum Length Sequence (MLS) signals. The theory behind MLS generation and use is well developed and does not involve computational problems. When a non-linear system is measured, the distortion appears in the deconvolved impulse response as a series of peaks distributed over time, in deterministic positions. In case of presence of noise during the measurement, the phase of any spurious noise, even an impulsive one, is randomly distributed over the entire length of the recovered impulse response. The ESS signal shows some advantages over MLS, such as a better signal to noise ratio (SNR) and a robust non-linearity rejection. Typically, in the same conditions, the ESS has a dynamic range of about 15 dB higher than MLS. Nonetheless, the generation of an ESS signal and the subsequent analysis of impulse responses involve some problems whose solutions are not yet common practice and short impulsive noises can contaminate the sampled data, causing bad effects on the deconvolved impulse response, in form of a frequency decreasing sweep. For the above mentioned reasons ESS is generally more suitable than MLS for use in architectural acoustics, but in some cases the use of MLS signal is still to be preferred. Differences and advantages between impulse response measurements obtained by means of MLS or ESS, are analyzed and discussed in this paper and an in-depth analysis of both measurement methods is presented. Some case studies of impulse response measurements performed inside historical Italian opera houses using both MLS and ESS, in non-ideal conditions (for example in presence of spurious noise), are presented and examined, highlighting differences, advantages and pitfalls of both measurement methods.